2022
DOI: 10.1038/s41467-021-27683-w
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages in epididymal adipose tissue secrete osteopontin to regulate bone homeostasis

Abstract: Epididymal white adipose tissue (eWAT) secretes an array of cytokines to regulate the metabolism of organs and tissues in high-fat diet (HFD)-induced obesity, but its effects on bone metabolism are not well understood. Here, we report that macrophages in eWAT are a main source of osteopontin, which selectively circulates to the bone marrow and promotes the degradation of the bone matrix by activating osteoclasts, as well as modulating bone marrow-derived macrophages (BMDMs) to engulf the lipid droplets release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 62 publications
1
34
0
Order By: Relevance
“…Patients with sarcopenia hiding in the normal BMI population were the confounding factor that created a false impression of the “obesity paradox”; therefore, BF% might be a better indicator for obesity diagnosis in old people. From the current results, the “obesity paradox” did not exist in old people with obesity defined by BF%, which was consistent with basic science studies and underlying molecular mechanisms ( 11 ). From the odds ratio results, sarcopenia is more associated with age-related osteoporosis than obesity, which emphasized the role of muscle in osteoporosis ( 46 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Patients with sarcopenia hiding in the normal BMI population were the confounding factor that created a false impression of the “obesity paradox”; therefore, BF% might be a better indicator for obesity diagnosis in old people. From the current results, the “obesity paradox” did not exist in old people with obesity defined by BF%, which was consistent with basic science studies and underlying molecular mechanisms ( 11 ). From the odds ratio results, sarcopenia is more associated with age-related osteoporosis than obesity, which emphasized the role of muscle in osteoporosis ( 46 ).…”
Section: Discussionsupporting
confidence: 91%
“…However, when body composition of fat and lean mass is taken into consideration, body fat mass is negatively associated with BMD in the younger population, while lean mass plays a positive role ( 10 ). In animal models, diet-induced obesity impairs bone turnover through cytokines and osteopontin secreted by adipose tissues, which activate osteoclasts and accelerate bone degradation ( 11 ). On the other hand, strain induced by muscle contraction stimulates bone growth as osteoblasts are mechanosensitive ( 6 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dai et al. ( 39 ) found that OPN secreted by the macrophages in epididymal white adipose tissue regulated the bone metabolism in high-fat diet (HFD)-induced obesity. The OPN selectively circulated to the bone marrow and promoted the degradation of the bone matrix by activating osteoclasts, both surgical removal of epididymal white adipose tissue and local injection of OPN-neutralizing antibodies or drugs aimed to deplete macrophages could ameliorate HFD-induced bone loss in mice.…”
Section: The Structure and Function Of Opnmentioning
confidence: 99%
“…Macrophages also promote the synthetic effects of parathyroid hormone (PTH), a key regulatory hormone of bone homeostasis, in bone tissue [ 154 , 155 ]. Macrophages in white adipose tissue are involved in the secretion of osteopontin, which may be a potential pathway for the treatment of obesity-associated bone disease [ 156 ]. Thus, macrophages may further coordinate bone homeostasis through the macrophage-osteoblast axis.…”
Section: Effect Of the Macrophage–osteoblast Axis On Bone Homeostasismentioning
confidence: 99%